PENGARUH SERVICESCAPE TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN SABOTEN SHOKUDO (Studi Kasus Pada Rumah Makan Saboten Shokudo Jalan Dieng Kota Malang) - Widyaningtyas, Nurul; Sudiro, Acmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determined the influence of servicescapeÂ (layout navigation, cleanliness, seating comfort, interiorÂ decor, and ambience) to the consumer satisfaction the Saboten Shokudo Restaurant at Dieng Street in Malang City. This type of research is explanatory research. The data collection of this study using a questionnaire. The study population were consumers Saboten Shokudo Restaurant at Dieng Street in Malang City. The sampling technique was conducted with insidental sampling technique. Respondents in this study are determined based on the opinions Roscoe, as many as 60. Regression analysis was used to test theÂ influence of the independent variables of the study (layout navigation, cleanliness, seating comfort, interior decor, and ambience) on the dependent variable of the study (consumer satisfaction). The results of this study indicate that the layout navigation, cleanliness, seating comfort, interior decor, and ambience influence simultaneously to the consumer satisfaction the Saboten Shokudo Restaurant at Dieng Street in Malang City. The layout navigation, cleanliness,and ambience are not influence partially, but seating comfort and interior decor are influece partially to the consumer satisfaction the Saboten Shokudo Restaurant at Dieng Street in Malang City. Dominant effect is a interior decor variable. that suggested a need to increase servicescape of all variables , especially the interior decor , to retain customers and reach new customersKeyword: servicescape, consumer satisfaction